Seedless, Etchless Deposition of Nanocrystalline Diamond Coatings for Performance Improvements of Micro End Mills using Carbon Ion Implantation - Torres, Christopher D.; Heaney, Patrick J.; Sridharan, Kumar; Cao, Guoping; Sumant, Anirudha V.; Carpick, Robert W.; Pfefferkorn, Frank E. (6th International Conference on MicroManufacturing (ICOMM 2011), 2011)
This study compares the cutting performance of (1) as-received uncoated, (2) acid etched plus seeded plus nanocrystalline diamond (NCD) coated, (3) carbon ion implanted (CII) plus NCD coated, and (4) only CII micro end mills.
Keywords: carbon ion implantation; nanocrystalline diamond; micro end milling